Penelitian Kerusakan Pada Sebuah Pipa Ketel Uap - Adnyana, D.N. (MESIN, 2007)
Failure Investigation on Ruptured Boiler Tube, This paper presents a failureinvestigation on a ruptured steam boiler tube. This boilertubewas madeoflow carbonsteel, having 76.1mm outside diameter and 5 mmthickness. Theboiler tube was installed in horizontal position on thefrontrear walls ofa steam boiler that was operated at steam pressure and temperature of60 bar and 275"C.respectively. The failure investigation was carried out by performing a number of examinationsincluding: macroscopy, metallography, hardness test and scanning electron microscopy (SEM) equippedwith EDS (energy dispersive spectroscopy). Results ofthefailure investigationshowed that thefailure onthe boiler tube was most likely caused by a short term localized overheating. The overheatingtemperature was estimated to have reached about 700 - 850Â°C. This was indicated by the formation ofbainite and/or martensite microstructure in some location of the ruptured tube material. Since no anysignificant scaleformation was observed in the tube internal wall, andalso no anyobvious indication ofpossible overheating due to a direct burner flame impingement toward the tube outside surface, it wastherefore concluded that the occurrence of short term localized overheating on the tube was mostprobably caused by low water level inthat particular part ofthe boiler tube.